Analysis of Passenger Willing to Use Urban Public Transportation During Covid-19 - Eridhita Kristhya Devianti; Atik Wahyuni; Farida Hardaningrum (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2022)
The rapid acceleration of population growth in the city of Surabaya has resulted in an increase in the number of users of transportation modes. The COVID-19 pandemic is a problem that has a major and global impact in Indonesia, especially in the transportation sector. The safety and comfort factor of passengers is one aspect that the people of Surabaya rethink before taking public transportation. Suroboyo Bus is one of the modes of public transportation that has directly felt the impact of the COVID-19 pandemic. There are policies implemented by the Government such as limiting the number of passengers and implementing health protocols. Therefore, the purpose of this study is to review and analyze the level of willingness of passengers on the West- East route of the Suroboyo Bus public transportation. The research method used to determine the greatest impact of the COVID-19 pandemic on passenger willingness is to conduct a survey of passenger respondents regarding socio-economic characteristics, passenger travel characteristics, and mode selection characteristics (Stated Preference). Processing and analyzing data using descriptive analysis with the Stated Preference (SP) method by distributing questionnaires totaling 100 samples to the general public for Suroboyo Bus passengers. The other data analysis methods used in this study are the Slovin formula method to determine the number of samples, validity and reliability tests used in testing questionnaires with Microsoft Excel tools. The results of the descriptive analysis of the characteristics of 100 respondents socio-economic passengers on the choice of the mode of Suroboyo Bus who travel is dominated by women with a productive age range of 21-30 years, the last education is SMA/SMK/MA, student work, monthly income <Rp 1,000. 000. While the results of the analysis of the characteristics of passenger travel come from Surabaya, the purpose of travel, the reason for using the mode is the cost/fare/ticket. And the analysis of the characteristics of mode selection with both facility attributes and service attributes during normal and pandemic times chooses the option "definitely chooses to be equipped with covid-19 facilities" and the results of the following analysis show that Suroboyo Bus passengers are still enthusiastic about this mode of transportation with covid facilities or facilities -19 adequate and also low cost and affordable for the general public.